2021
DOI: 10.3389/fimmu.2021.707977
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Profiling Reveals the Critical Antigenic Determinants in SARS-CoV-2 RBD-Based Antigen

Abstract: The ongoing COVID-19 pandemic caused by SARS-CoV-2 is a huge public health crisis for the globe. The receptor-binding domain (RBD) of SARS-CoV-2 spike (S) protein plays a vital role in viral infection and serves as a major target for developing neutralizing antibodies. In this study, the antibody response to the RBD of SARS-CoV-2 S protein was analyzed by a panel of sera from animals immunized with RBD-based antigens and four linear B-cell epitope peptides (R345, R405, R450 and R465) were revealed. The immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 54 publications
3
31
0
2
Order By: Relevance
“…To our knowledge, it is not yet known whether the SARS-CoV-2 spike residues 616/644 and 1138/1169 contribute to the protective efficacy of Pfizer-BioNTech COVID-19 vaccine comirnaty 23 , 31 34 , 37 , 38 . There is some evidence that potent neutralization of SARS-CoV-2 requires both spike conformational changes and receptor blockade elicited by antibody binding 10 , 13 18 , 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, it is not yet known whether the SARS-CoV-2 spike residues 616/644 and 1138/1169 contribute to the protective efficacy of Pfizer-BioNTech COVID-19 vaccine comirnaty 23 , 31 34 , 37 , 38 . There is some evidence that potent neutralization of SARS-CoV-2 requires both spike conformational changes and receptor blockade elicited by antibody binding 10 , 13 18 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of information on the protection conferred by the S2P6 peptide-reactive antibodies against SARS-CoV-2 infection, the data obtained with the B-cell epitope S2P6 peptide broadens our understanding on the efficacy of COVID-19 mRNA comirnaty vaccine. Finally, our study raises the question on the medical applicability of a vaccine formulation based on linear B-cell epitope peptides, e.g., the S2P6 peptide containing the residues 1138/1169 located in the C-terminal region of S2 subunit from SARS-CoV-2 spike protein 37 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For SARS-CoV-2, Jiang et al analysed the RBD-specific Ab response from a panel of sera from animals immunised with RBD-based antigens and identified four linear B cell epitope peptides: 350VYAWN345, 407VRQIAP412, S450-469 and 473YQAGSTP479 [66]. Three immunodominant peptides, 350VYAWN345, 407VRQIAP412 and 473YQAGSTP479, were revealed to induce a potent Ab response to the SARS-CoV-2 S protein in the mouse model.…”
Section: Alternative Candidates For Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…The M proteins and nucleoproteins of influenza were revealed to be more conserved than the proteins exposed on the viral surface, such as haemagglutinin and neuraminidase. Moreover, Patel et al reported that the T cell immune response elicited by the conserved influenza epitopes may enhance the broad-spectrum efficacy of the pan-influenza vaccine [66]. Although further investigations are required to examine if these discoveries are applicable in designing a pan-coronavirus vaccine, these studies suggest that the non-S proteins of SARS-CoV-2 may be suitable in stimulating robust anti-viral T cell immune responses and are less susceptible to genetic drift.…”
Section: Pan-coronavirus Vaccinementioning
confidence: 99%
See 1 more Smart Citation